Prognostic Factors and Survival Rates in Early-stage Cervical Cancer Patients Treated with Radical Hysterectomy and Pelvic Lymphadenectomy - Ploypailin Thanabhinunt (Thai Journal of Obstetrics and Gynaecology, 2018)
Objectives: To evaluate prognostic factors and survival rates in early-stage cervical cancer patients who had been treated with radical hysterectomy and pelvic lymphadenectomy (RHPL).Materials and Methods: Medical records and pathologic findings of 177 cervical cancer patients who had International Federation of Gynecology and Obstetrics (FIGO) stage IA2-IIA and underwent RHPL at Buddhachinaraj Phitsanulok Hospital from January 2005 to December 2016 were retrospectively reviewed. Clinicopathologic variables and treatment data were collected.Results: Among 177 patients, mean age was 49.9 ± 11.0 years. The median follow-up time was 42 months. Twenty-five patients had a recurrence and 7 patients died from disease. A five-year disease free survival (DFS) rate and a 5-year cancer-specific survival (CSS) rate were 89% and 96.6%, respectively. The independent prognostic factors for DFS were increasing age and pelvic lymph node metastasis (hazard ratio [HR] 1.06; 95%CI 1.02-1.10, and HR 4.63; 95%CI 1.21-17.64, respectively). No significant differences in FIGO stage, histology, positive surgical margin, parametrial involvement, pelvic lymph node metastasis, deep stromal invasion, lymph vascular space invasion, and tumor size were identified as independent prognostic factors for CSS. However, adenocarcinoma (AC) patients with parametrial involvement, pelvic lymph node metastasis, and postoperative treatment followed by concurrent chemoradiotherapy (CCRT) had a significantly worse survival outcome than those with squamous cell carcinoma (SCC) (HR 11.87; 95%CI 1.46-46.20, HR 7.00; 95%CI 1.55-31.66, and HR 7.20; 95%CI 1.57-32.85, respectively). Conclusion: Early-stage cervical cancer patients who underwent RHPL showed good survival rates. The independent prognostic factors for DFS were increasing age and pelvic lymph node metastasis whereas no prognostic factors for CSS were found. Furthermore, parametrial involvement, pelvic lymph node metastasis, and postoperative treatment followed by CCRT were likely to be predictors for poorer survival outcomes in AC than those in SCC.